PENGARUH LAYANAN M-BANKING TERHADAP KEPUASAN NASABAH - Angel Simatupang; Hani Hatimatunnisani; Hasdilla Syafitri; Rifki Paturohman; Kunto Ajibroto (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2024)
The aim of this research is to analyze the influence of M-Banking services on customer satisfaction. The type of research used is quantitative with descriptive methods. A sample of 56 respondents was taken randomly using a questionnaire. The results show that M-Banking services have a positive and significant effect on customer satisfaction. The existence of M-Banking services helps customers speed up transactions, so that the process can be carried out more flexibly and efficiently. However, service provider banks need to pay better attention to user security and handling online complaints in order to increase customer satisfaction.